(untitled) (Scientific journal of the Fergana State University, 2025)
The article discusses flavonoids, which are polyphenolic compounds, found in the leaves and seeds of local grape varieties. Our scientific research was conducted using high-performance liquid chromatography (HPLC). The local grape varieties, including Husayni, Kelin Barmoq, and Rizamat, were selected as samples, specifically their spring and autumn leaves and seeds. The article also provides information on the flavonoids found in grape varieties cultivated in other regions, as well as various types of these compounds. Based on the data presented, the results obtained during our research have been analyzed.